17 years of coastline changes observation in the Northern part of Rupat Island using Landsat 7 ETM + time series imagery (2000-2017); a case study of the country’s border between Indonesia - Malaysia - Kausarian, Husnul; Batubara, Ahmad Rifai; Astuti, Puji; Sumantyo, Josaphat Tetuko Sri; Lubis, Muhammad Zainuddin (Penerbit Universiti Kebangsaan Malaysia, 2023)
Rupat Island is the outermost part of Indonesia which borders Malaysia. This island is part of Bengkalis Regency, Riau Province, located at 02° 4.911’N-101° 27,191’E. This study uses primary data from field observations and secondary data in Landsat 7ETM+ Time Series image data and other supporting data. The descriptive method is carried out in the form of geological interpretation in the field, determination of validation points and then analysis using GIS/visual interpretation to obtain shoreline changes that occurred in the northern part of Rupat Island from the year 2000 to 2017. Additional data used were sea current and pattern and wind direction and speed. Validation points are used to obtain detailed calculations related to this coastline change: Tanjung Api area to Teluk Rhu and Tanjung Lapin get the measurement results experienced the most accretion occurred in 2013 was 167.21 m, and the most abrasion in 2016 was 72.77 m. The biggest change occurred in 2013 when the accretion occurred at 375.5 Ha, and the most abrasion occurred in 2014 at 50.63 Ha. Meanwhile, for shoreline changes, the minimum annual coastline length in 2004 was 19.04 km, and the normal coastline length in 2015 was 28.26 km. The maximum length of the coastline occurred in 2013 was 36.53 km.